Physical properties of single jersey bamboo cotton fabric produced on home knitting machine / Ainil Huda Abu Talib… [et al.] - Abu Talib, Ainil Huda; Misron, Siti Nuranis Syazana; Mohd Fu’ad, Nurul ‘Izzah; Zamri, Nurul Ariesha; Nasir, Eryna (Univeristi Teknologi MARA, Sabah, 2020)
The Silver Reed Model LK150 knitting machine is a home knitting machine which is extremely lightweight and compact, making it preferable by most home knitters. There are various knitwears with interesting patterns can be made using this model. In the field of garments manufacturing by using flatbed knitting machines, it is important to understand the physical properties of fabric so that their impact on dimensional changes can be predicted to produce the most suitable end use. The samples were produced by using a blended bamboo/cotton yarn, with a composition of 30% cotton and 70% bamboo. The main objectives of this study are to to evaluate the physical properties of single jersey fabric knitted on home knitting machine by using different stitch dials and to relate the physical properties with different stitch lengths. Then, all tests were conducted to compare the physical properties of samples between three different stitch dials and the effects of before and after washing. The physical properties measured in this research were stitch length, stitch density, weight, thickness, absorbency and shrinkage. The result indicated that the longer the stitch length, the higher the percentage of the water impact penetration. Meanwhile, there was a slight reduction on the density, thickness and fabric weight. In addition, the result after three times washing showed that the samples only had slight changes in density, thickness, weight and stitch length, but has significant changes on the water impact penetration.